Teachers’perceptions of the relationship between principals’ instructional leadership, school culture and school effectiveness in secondary schools in Pakistan / Niaz Ali - Ali, Niaz (2017)
This study is aimed at investigating the relationship of school principals’ Instructional Leadership (IL) on School Effectiveness (SE) and to question whether this relationship is direct or indirect, through the mediation of School Culture (SC). This study is basically a co-relational study, with the main focus revolving around the relationship between the IL, SE, and SC in secondary schools in Pakistan. The research design is a non-experimental design with a survey study. A survey instrument (questionnaire) comprising of 62 items was used to collect data for IL, SC, and SE. The questionnaire was distributed among 367 teachers of secondary schools in Mardan district of Khyber Pukhtunkhwa province of Pakistan. The data collected was analysed with the help of statistical tools, the SPSS and AMOS. The demography of respondents was 235 (64%) male and 132 (36%) female from 84 (81.55%) rural schools and 19 (18.44%) urban schools. With respect to the urban and rural school division, the total number of the respondents (male and female) from rural secondary schools was 270 (73.6%) and from urban secondary schools was 97 (26.4%). The respondents have different ages, experience and qualifications, and the majority (52.9%) have a rich service experience1. Results of this study show that the instructional leadership in these schools is at present, at a low level. Similarly, the school culture was found to be developing, but in contrast the level of school effectiveness was found to be moderate. This study has revealed that even where there is a low level of IL and SC, school effectiveness is still possible. It is proposed therefore that if the instructional leadership and school culture are increased to a high level, the level of school effectiveness will increase considerably. The results show that school culture can contribute to enhanced school effectiveness of the stated secondary schools. Correlation among the three variables and the related dimensions provides important information that the IL skills are required to improve SC and SE in the stated secondary schools. Although, the correlation among all the three variables (IL, SC, & SE) is high, the correlation between IL and SC is the highest. The conceptual model used is the integration of principal’s instructional leadership, school culture, and school effectiveness. Age of the respondents has proven to be the moderator for the stated relationship. This study offers a significant contribution to the leadership literature in a developing country like Pakistan. The study provides a road map for self-development of the education system in secondary schools in Pakistan. The findings of this study would suggested that principals should develop a positive school culture for effectiveness; the ultimate goal of a school.